Treatment of anklejoint injuries from position of biological medicine - Shuba, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2020)
Injuries of capsule-ligamentous tissues in the structure of ankle joint trauma are 70–75 %. The consistent symptom in case of ankle joint capsule injury is a posttraumatic edema, which is treated usually with conservative methods (drugs on the basis of aescinum, hand lymphatic drainage, elastic bandages or stocking, exercises for stimulation of «muscular pump»). Perspective is the applying for treatment of bioregulation drugs. Objective: to conduct the comparative analysis of dynamics of posttraumatic edema and pain regression in patients with ankle joint injuries with ITIRES medication («PEKANA Naturheilmittel GmbH», Germany) and reference drug of base therapy. Methods: we included 30 patients (middle age (39.4 ± 8.3) of years) with ruptures, tensions and overstrains of capsule-ligamentous tissues of ankle joint (S93.2, S93.4 on International Classification of Diseases 10th Revision). Patients were divided into two groups: Р (15 patients) — combination of ITIRES drug (drops, ointment) was used during 14 days, C (control, 15 patients) — standard antiedemic drugs on the basis of aescinum. We studied the changes of volume of the damaged extremity. Results: for the patients of group Р an antiedemic effect was marked already on the third day after trauma. On the 5th day the volume of the damaged extremity of relatively initial size was reduced on the average on 7 % against 1 % (р < 0.05) compare to control group. At the end of the first week of posttraumatic period the mean value of volume diminished on 11.9 % in a group Р compare to 1.7 % in a group C, on the 14th day — 18.3 % compare to 9.5 %. Decreasing of pain syndrome intensity for the patients of the group Р was observed on the end of the 3rd day period day with subsequent reducing to the 5th day; in the control group — on the 7th day period. Conclusions: efficiency of ITIRES application is shown in complex therapy of posttraumatic edema for patients with the ankle joint injuries.